Intergenerational Pathways into Family Sex Market Facilitation - Horning, Amber (Victims & offenders, 2024)
Prior studies have found that 15–31% of sex market facilitators (SMFs) experienced family trafficking, and this was a primary route of market entrance (Dank et al., 2014), yet researchers have not thoroughly explored this social problem. We interviewed 24 SMFs exposed to facilitation through family, starting as teenagers. We qualitatively explored the accounts using the Grounded Theory (G.T.) approach (Glaser & Strauss, 2017), evaluating patterns to their entrance story using the sensitizing concept of “agency.” Our sample consisted of SMFs experiencing structural disadvantage. Their positionality informed their formulations of their entrance, ranging from family coercion to cooperative learning. Their negative formulations centered on being denied a childhood, exposure to negative stimuli, physical or sexual abuse, unconventional relationships with caregivers, strained relationships with traditional family and family discord. At the same time, their positive interpretations centered on family bonding, masculinity, survival, career, status, and freedom. Our findings indicate that prevention programming should be implemented at the community and family levels to address structural inequality contributing to fragile family systems, risk, trauma, and destructive relationship cycles. Policy directives and legislation should consider these social actors exploited and include them in prevention programs.